Germination of hibiscus sabdariffa L. seeds after storage under different environments - Jovinia, binti Jowinis. (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study was conducted to evaluate the effects of storage environments on germination of Hibiscus sabdariffa L. seeds. Seeds with 8.9% of moisture content and 93% ofgermination were placed in four different environments; ambient room (28-30°C), air-conditioned room (22-23°C), refrigerator (3-4°C) and incubator (38-40°C) for 14 days. Seed stored in air-conditioned room gave the highest moisture content and germination with 7.70% and 91% respectively. Storage in incubator showed gradual decrement of moisture content and germination throughout the period of storage. Generally, moisture content and germination percentages decreased with increase in storage period. Regression analysis indicated that seeds stored in airconditioned room can maintain its germinability up to 8 months and II days. Results showed that storage in air-conditioned room was a suitable condition to store H. sabdariffa seeds.